Dósis de compost de residuos sólidos orgánicos domiciliarios en el rendimiento de Solanum lycopersicum Mill, tomate, variedad regional. Loreto.2024 - Da Silva Ramirez, Jomyra Simona Del Rosario (2025)
The study was carried out in Loreto, a region rich in biodiversity, where the climate is hot with high rainfall and the soil is Clay Loam, with an extremely acidic pH and low fertility. The experiment proceeded with different levels of manure per ha of 30, 40, 50 and 60 t. The experimental units in number of 16 distributed in four replications taking into account the DBCA statistical design and the Tukey Test that allowed us to make statistical comparisons between the treatments proposed in the study. The results obtained led to the conclusions that the application of compost from household organic solid waste in the yield of regional variety tomato had a significant effect; the T4 treatment, which was applied 40 t/ha per hectare, proved to be the most influential in the agronomic characteristics of the crop; A progressive improvement in agronomic characteristics was observed as the compost dose of household organic solid waste was increased; The results indicated that compost from organic solid waste from the house could be a useful resource to increase the yield and agronomic characteristics of tomatoes in cultivation systems; the application of 40 t of compost/ha (T4), presented the best yields in fruit weight, of 67 g; fruit weight/plant; of 1,746 g and weight of fruits/ha, of .34,920 Kg/ha; T4 obtained the best productivity in the cultivation of tomato regional variety of S/. S/.14,772.4